Echis coloratus envenomation in a dog: clinical, hemostatic and thromboelastometric findings and treatment. (3rd July 2021) - Atamna, Raya; Kelmer, Efrat; Aroch, Itamar; Klainbart, Sigal
Abstract: Context: Echis coloratus is endemic to the Middle East. Clinical reports describing E. coloratus envenomation in humans are scarce, while natural envenomations of animals were not reported. Such envenomations may induce systemic coagulopathy. This report describes a confirmed E. coloratus envenomation in a dog, with assessment of the global hemostasis by thromboelastometry. Case details: A 6-year old Belgian Shepherd dog was presented in shock, mucosal bleeding and swelling due to snakebite. Laboratory tests showed prolonged prothrombin and activated partial thromboplastin times. Because Daboia palaestinae is the most common venomous snake in Israel, immunoglobulin-G monovalent D. palaestinae antivenom was administered, with supportive care. The dog improved clinically, was discharged, and was readmitted, with active bleeding from the bite site. The dead snake was only then identified as E. coloratus . Thromboelastometry demonstrated severe hypocoagulability. The dog was treated with polyvalent antivenom directed against venoms of several Middle Eastern snakes, fresh-frozen plasma and packed red blood cells. Bleeding completely ceased, and thromboelastometry results improved. The dog was discharged. 3 days later, all hemostatic test results had normalized. Discussion: Thromboelastometry is useful for assessing the hemostatic status in E. coloratus envenomation, and for monitoring and managing the venom-induced coagulopathy, and guide plasma and polyvalent antivenom treatment.